Microglia morphophysiological diversity and its implications for the CNS - Vidal-Itriago, Andrés; Radford, Rowan A. W.; Aramideh, Jason A.; Maurel, Cindy; Scherer, Natalie M.; Don, Emily K.; Lee, Albert; Chung, Roger S.; Graeber, Manuel B.; Morsch, Marco (Frontiers in Immunology, 2022)
Microglia are mononuclear phagocytes of mesodermal origin that migrate to the central nervous system (CNS) during the early stages of embryonic development. After colonizing the CNS, they proliferate and remain able to self-renew throughout life, maintaining the number of microglia around 5-12% of the cells in the CNS parenchyma. They are considered to play key roles in development, homeostasis and innate immunity of the CNS. Microglia are exceptionally diverse in their morphological characteristics, actively modifying the shape of their processes and soma in response to different stimuli. This broad morphological spectrum of microglia responses is considered to be closely correlated to their diverse range of functions in health and disease. However, the morphophysiological attributes of microglia, and the structural and functional features of microglia-neuron interactions, remain largely unknown. Here, we assess the current knowledge of the diverse microglial morphologies, with a focus on the correlation between microglial shape and function. We also outline some of the current challenges, opportunities, and future directions that will help us to tackle unanswered questions about microglia, and to continue unravelling the mysteries of microglia, in all its shapes.